MySQL - DuBois, Paul (Que, 1999)
In MySQL, Paul DuBois provides you with a comprehensive guide to one of the most popular relational database systems. As an important contributor to the online documentation for MySQL, Paul uses his day-to-day experience answering questions users post on the MySQL mailing list to pinpoint the problems most users and administrators encounter. The principal MySQL developer, Monty Widenius, along with a network of his fellow developers, reviewed the manuscript, providing Paul with the kind of insight no one else could supply. Instead of merely giving you a general overview of MySQL, Paul teaches you how to make the most of its capabilities. Through two sample databases that run throughout the book, he gives you solutions to problems you'll likely face. He helps you integrate MySQL efficiently with third-party tools, such as PHP and Perl, enabling you to generate dynamic Web pages through database queries. He also teaches you to write programs that access MySQL databases.
Keywords: SQL (Computer program language); SQL (Langage de programmation)